Counting the costs of expensive tissues: mating system, brain size, and IGF-1 affect the ecological costs of transport in mammals - Husak, Jerry F.; Sorlin, Mahaut V.; Lailvaux, Simon P. (Frontiers in Ethology, 2024)
Although sexual selection can be a powerful evolutionary force in shaping the phenotype, sexually selected traits do not evolve in isolation of other traits or without influence from other selective pressures. Expensive tissues, such as brains, can constrain the evolution of sexually selected traits, such as testes, as can other energetically expensive processes, like the costs of locomotion. However, simple linear or binary analyses of specific traits of interest can prevent detection of important links within the integrated phenotype and obfuscate the importance of multiple selective forces. We used phylogenetically informed path analysis to determine causal links among mating system type, pace of life history, costs of locomotion, brain size, and testis size across 48 mammal species that exhibit a wide range of body sizes, life-history strategies, and types of locomotion. We found species with non-monogamous mating systems were associated with larger testes, faster life histories, and lower costs of locomotion compared to monogamous species. Having a larger brain was associated with a slower life history and, surprisingly, larger testes. In addition to highlighting the non-intuitive nature of certain causal relationships, our results also emphasize the utility of including multiple traits in studies of sexually selected traits, as well as considering the constraints imposed by linked traits and selection on those linked traits.